2019
DOI: 10.1103/physrevb.100.094446
|View full text |Cite
|
Sign up to set email alerts
|

Flat-band magnetism and helical magnetic order in Ni-doped SrCo2As2

Abstract: A series of Sr(Co1−xNix)2As2 single crystals was synthesized allowing a comprehensive phase diagram with respect to field, temperature, and chemical substitution to be established. Our neutron diffraction experiments revealed a helimagnetic order with magnetic moments ferromagnetically (FM) aligned in the ab plane and a helimagnetic wavevector of q = (0, 0, 0.56) for x = 0.1. The combination of neutron diffraction and angle-resolved photoemission spectroscopy (ARPES) measurements show that the tuning of a flat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…The above MFT discussion of helical ordering may be expected to be of only qualitative significance, since the MFT was formulated for local-moment AFMs instead of itinerant AFMs. However, magnetic neutron diffraction measurements [63,64] found that the magnetic structure is indeed helical, with helix turn angles that decrease from 104 • to 94 • on increasing x from x = 0.06 to 0.15, which have the same trend and are of the same order as we infer in Fig. 12 from Eq.…”
Section: B Molecular-field-theory Analysis Of Magnetic Susceptibility In the Ordered State In Terms Of Helical Afm Orderingsupporting
confidence: 73%
“…The above MFT discussion of helical ordering may be expected to be of only qualitative significance, since the MFT was formulated for local-moment AFMs instead of itinerant AFMs. However, magnetic neutron diffraction measurements [63,64] found that the magnetic structure is indeed helical, with helix turn angles that decrease from 104 • to 94 • on increasing x from x = 0.06 to 0.15, which have the same trend and are of the same order as we infer in Fig. 12 from Eq.…”
Section: B Molecular-field-theory Analysis Of Magnetic Susceptibility In the Ordered State In Terms Of Helical Afm Orderingsupporting
confidence: 73%
“…CaCo 2 As 2 shows Atype AF order with μ c [30], the occurrence of which is tied to partially flat electronic bands lying closer to the Fermi energy E F than for paramagnetic SrCo 2 As 2 [28]. The value of c changes with x for both Sr(Co 1−x Ni x ) 2 As 2 [32,33] and Sr 1−x Ca x Co 2 As 2 [36], and, interestingly, both series show regions of AF order with μ ⊥ c for ratios of c/a corresponding to their uncollapsed-tetragonal (ucT) phases [32,36]. The ucT phase is characterized by weaker As-As covalent bonding than in the cT phase [37].…”
mentioning
confidence: 94%
“…Recently, the electron-doped materials Sr 1−x La x Co 2 As 2 [31] and Sr(Co 1−x Ni x ) 2 As 2 [32,33] have been shown to develop long-range AF order for extremely low substitutions of x ≈ 1% as shown by the magnetic phase diagram in Fig. 1(a) for the Ni-doped series.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, non-Fermi-liquid types of behavior associated with a composition-induced magnetic quantum-critical point in Sr(Co 1−x Ni x ) 2 As 2 crystals near x = 0.3 has been reported [37]. In addition, crystals of Sr(Co 1−x Ni x ) 2 As 2 with 0 < x < 0.3 exhibit c-axis helical or spin-density-wave AFM ordering [37][38][39], which is quite unusual in itinerant antiferromagnets. A small amount (2.5%) of La doping has been reported to cause FM ordering in Sr 1−x La x Co 2 As 2 [40,41].…”
Section: Introductionmentioning
confidence: 99%